APHASIA IN NEUROLINGUISTICS STUDY: A PRELIMINARY STUDY - Riki Nasrullah; Nagita Ayu Windorika; Isti Choirunnisa Zalsabila; Anggi Nanda Gustina; Salwatus Sholehah; Nadinta Aulia Putri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Aphasia is a language disorder that occurs due to damage to the brain, which affects a person's ability to speak, understand, read, and write. It can affect various aspects of language, such as phonology, semantics, syntax, and pragmatics. Neurolinguistic studies have helped us understand more about aphasia and how damage to the brain affects language. The study of aphasia has provided insight into the organisation of language in the brain and how damage to certain areas can affect language ability. This article provides an initial overview of aphasia in neurolinguistic studies, discussing the definition and characteristics of this language disorder, as well as factors that affect language recovery after experiencing aphasia. Overall, this article aims to provide a basic understanding of aphasia in neurolinguistic studies and how this research can help us understand more about language and the brain.